A photothermal and Fenton active MOF-based membrane for high-efficiency solar water evaporation and clean water production. Issue 43 (26th October 2020) - Ma, Xu; Deng, Zheng; Li, Zhuoyi; Chen, Danke; Wan, Xinyi; Wang, Xiaobin; Peng, Xinsheng
Abstract : A Fenton active Zr–Fc MOF-based membrane was designed for efficiently producing clean water from VOC contaminated water via the solar evaporation process. Abstract : Solar-driven interfacial water evaporation (SDIWE) is a promising way to reduce the fresh water scarcity. However, it is still challenging to generate clean water from volatile organic compound (VOC) contaminated water via SDIWE. In this work, a free-standing MOF-based membrane (Zr–Fc MOF/SWCNT/gelatin, ZSG) with excellent photothermal properties and high Fenton catalytic activity is rationally designed for producing clean water from VOC contaminated water. Thanks to the hierarchical pore structure, excellent photothermal properties and good hydrophilicity of the ZSG membrane, an impressive water evaporation rate of 1.53 kg m −2 h −1 is achieved under 1 sun irradiation. Meanwhile, the Zr–Fc MOF has been demonstrated to be an efficient Fenton catalyst to promote the generation of ˙OH for degradation of methylene blue and phenol. As a result, the VOCs are degraded in situ to prevent their accumulation in the collected water, and the COD value of the regenerated water is lower than the drinking water hygiene standards. Besides, its salinity also meets the drinking water standards of the World Health Organization (1‰).